2011
DOI: 10.1021/jm101532u
|View full text |Cite
|
Sign up to set email alerts
|

Role of Metalation in the Topoisomerase IIα Inhibition and Antiproliferation Activity of a Series of α-Heterocyclic-N4-Substituted Thiosemicarbazones and Their Cu(II) Complexes

Abstract: The topoisomerase-IIα inhibition and antiproliferative activity of α-heterocyclic thiosemicarbazones and their corresponding copper(II) complexes have been investigated. The CuII(thiosemicarbazonato)Cl complexes were shown to catalytically inhibit topoisomerase-IIα at concentrations (0.3–7.2 μM) over an order of magnitude lower than their corresponding thiosemicarbazone ligands alone. The copper complexes were also shown to inhibit the proliferation of breast cancer cells expressing high levels of topoisomeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
149
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(153 citation statements)
references
References 34 publications
4
149
0
Order By: Relevance
“…Recent studies indicated that the thiosemicarbazones and their metal complexes had the ability to inhibit TOP2α These studies both reinforced the significant potential of metalthiosemicarbazonato complexes in cancer research and they also expanded the array of potential biochemical targets for those molecules (51)(52)(53)(54). R-Heterocyclic thiosemicarbazones and their Cu(II) complexes are capable of in vivo and in vitro inhibition of TOP2α at an IC 50 below that of the widely employed TOP2α poison etoposide (VP-16).…”
Section: Top2α Inhibitorsmentioning
confidence: 94%
“…Recent studies indicated that the thiosemicarbazones and their metal complexes had the ability to inhibit TOP2α These studies both reinforced the significant potential of metalthiosemicarbazonato complexes in cancer research and they also expanded the array of potential biochemical targets for those molecules (51)(52)(53)(54). R-Heterocyclic thiosemicarbazones and their Cu(II) complexes are capable of in vivo and in vitro inhibition of TOP2α at an IC 50 below that of the widely employed TOP2α poison etoposide (VP-16).…”
Section: Top2α Inhibitorsmentioning
confidence: 94%
“…The PC-9, Eca-109 and SGC-7901 cell lines were seeded into 6-well plates at a density of 1x10 6 cells/well and incubated overnight at 37˚C in a humidified atmosphere containing 5% CO 2 . Cells were treated by the TSCs with each corresponding half maximal inhibitory concentration (IC 50 ) dose for 24 h. Following treatment, all the cell samples were washed twice with PBS and lysed in sample buffer.…”
Section: General Synthesis Procedures Of Tscs 1a-ementioning
confidence: 99%
“…Among TSCs, (N)-heterocyclic TSCs have been extensively investigated as potential anticancer agents, and 3-aminopyridine-2-carboxaldehyde TSC (3-AP or triapine) is currently undergoing phase II clinical trials (4). It has been confirmed that TSCs play essential antitumor roles through numerous mechanisms, including ribonucleotide reductase inhibition (5,6), metal-dependent radical damage (4), DNA binding (7) and inhibition of protein synthesis (8). However, it should be noted that the biological activities of TSCs often show a high dependence on their substituents (1,4).…”
Section: Introductionmentioning
confidence: 99%
“…Lately, Brian M. Zeglis's group notified the role of metalation of thiosemicarbazone analogs in the topoisomerase IIα inhibition and anti-proliferation activity. [31,32] In view of the above-mentioned facts, and as a resumption to our work on the preparation of biologically active complexes, we were prompted to synthesize Cu(II), Ni(II), Co(II), Zn(II),Mn(II), VO(II) and Cd(II) complexes of 2-[(4,9-dimethoxy-5-oxo-5H-furo[3,2-g] chromen-6-yl) methylene]-hydrazinecarbothioamide in an attempt to promote the anti-cancer activity for these compounds on human cell lines, with particular attentiveness to the causative relationship of ROS induction in the cells.…”
Section: Introductionmentioning
confidence: 99%